Mouse and Pig Models for Studies of Natural and Vaccine-Induced Immunity to Bordetella pertussis. - MILLS, KINGSTON (My University, 2014)
The increasing incidence of whooping cough in many developed countries has been linked with waning immu- nity induced after immunization with acellular pertussis (aP) vaccines. The rational design of an improved aP vaccine requires a full understanding of the mechanism of protective immunity and preclinical studies in animal models. Infection of mice and pigs with Bordetella pertussis has many features of the infection seen in humans and has already provided valuable information on the roles of innate and adaptive immune responses in protection. Recent findings in these models have already indicated that it may be possible to develop an improved aP vaccine based on a formulation that includes a Toll-like receptor agonist as an adjuvant
PUBLISHED
Keywords: adjuvant; Tcells; protective immunity; vaccine; respiratory infection; animal model; whooping cough; Bordetella pertussis; Immunology, Inflammation & Infection